Making and testing the carhart-clark standard cell - Nichols, Schuyler (My University, 1898)
Introduction: The materials necessary to the construction are – 1. A glass specimen or test tube about three-fourths inch in diameter and three inches long; 2. A piece of platinum wire about two or three inches long; 3. A rod of pure zinc about two inches long; 4. Two six-inch pieces of copper wire; 5. Pure mercury; 6. mercurous sulphate; 7. zinc carbonate; 8. zinc sulphate; 9. fur odds and ends. In constructing the cell, first seal the platinum wire into the closed end of the specimen or test tube so that about one inch of it is within the tube. A piece of glass tubing of proper diameter and length may be used instead of the specimen or test tube, by closing one end in the blow pipe flame. In this case the platinum wire may be sealed in at the time of closing the end. This sealing in of the platinum wire may be avoided by using a piece of capillary tubing three inches long and sealing the wire into one end of it. Then fasten the capillary tube to the inside of the cell chamber with cement or by cohering it fast when in a plastic condition from heating. The wire should project about an inch from the end of the capillary tube and bottom of tube should be within one half inch of bottom of cell chamber.
Citation: Nichols, Schuyler. Making and testing the carhart-clark standard cell. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Testing; Capilary Tube; Test Tube; Carhart-Clark Standard Cell; Theses